PENDEKATAN TEKNOLOGI BERBASIS ANDROID UNTUK MENINGKATKAN LITERASI BUDAYA SISWA SEKOLAH DASAR - Darmuji, Darmuji; Saputra, Muhammad Hadi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Local cultural literacy is a crucial aspect that should be instilled from an early age to shape the identity and character of the younger generation. However, in today’s digital era, conventional learning methods tend to be less engaging for students. This study aims to develop an interactive and engaging Android-based learning media for teaching Jambi culture. The research uses a Research and Development (R&D) approach, employing the ADDIE development model consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The application contains local content including folktales, regional songs, traditional games, and interactive evaluation quizzes. The trial was conducted with fourth and fifth-grade elementary students in several schools in Jambi City. The results showed a significant improvement in students’ learning interest and understanding of Jambi culture. This innovation is expected to serve as an effective alternative solution for teaching local content through digital technology-based learning. Keyword: cultural literacy, digital learning, Jambi culture, Android, elementary education. Abstrak: Literasi budaya lokal menjadi aspek penting yang perlu ditanamkan sejak usia dini untuk membentuk identitas dan karakter generasi muda. Namun demikian, di era digital saat ini, metode pembelajaran konvensional cenderung kurang diminati oleh siswa. Penelitian ini bertujuan mengembangkan media pembelajaran budaya Jambi berbasis Android yang bersifat interaktif dan menarik. Metode yang digunakan adalah Research and Development (R&D) dengan model pengembangan ADDIE yang terdiri dari lima tahap: Analysis, Design, Development, Implementation, dan Evaluation. Aplikasi ini memuat konten lokal yang mencakup cerita rakyat, lagu daerah, permainan tradisional, dan kuis evaluasi berbasis interaktif. Uji coba dilakukan pada siswa kelas IV dan V di beberapa sekolah dasar di Kota Jambi. Hasil penelitian menunjukkan peningkatan signifikan dalam minat belajar dan pemahaman siswa terhadap budaya Jambi. Inovasi ini diharapkan menjadi solusi alternatif yang efektif dalam pembelajaran muatan lokal berbasis teknologi digital. Kata kunci: literasi budaya, pembelajaran digital, budaya Jambi, Android, pendidikan dasar.